The Impact of Credit Risk, Market Risk, and Operational Risk on Bank Financial Performance with State Ownership as a Moderating Variable in Indonesia (2020-2024) - Arif Sariputra; Oktavia Oktavia (Green Publisher Indonesia, 2026)
This research analyzes the impact of credit risk, market risk, and operational risk on the financial performance of Indonesian commercial banks, and examines the moderating role of state ownership across the pandemic (2020–2021) and post-pandemic (2022–2024) periods. Using quantitative panel data regression on 34 conventional banks, credit risk is proxied by non-performing loans (NPL) and loan loss provisions; market risk by market-based income and securities portfolios; and operational risk by BOPO and operating expenses to total assets. Financial performance is measured by Return on Assets (ROA), with state ownership as a moderator. The results indicate that the relationship between risk and financial performance is dynamic and state-dependent. Credit risk shows varying effects across indicators and periods, with one indicator remaining significantly negative during the pandemic while both indicators become significantly negative in the post-pandemic period. Market risk exhibits a selective effect, with market-based income consistently contributing positively to financial performance, while securities portfolio exposure does not show stable effects. Operational risk is found to be the most consistent factor influencing financial performance across all periods. Furthermore, state ownership has a direct effect on financial performance and plays a moderating role that varies across risk types: it tends to strengthen the effect of credit risk, weaken the effect of market risk, and significantly influence the relationship between operational risk and financial performance. These findings suggest that the relationship between risk and bank performance is not static, but is shaped by economic conditions and ownership structure.